Tracking the Impact of Local Wisdom in Sustainable Cultural Heritage Conservation: A Bibliometric Approach - Hayu Lusianawati; Sabil Mokodenseho; Dedi Gunawan Saputra; Yenik Pujowati (Westscience Press, 2023)
In order to track the contribution of local wisdom to sustainable cultural heritage preservation, this study uses a bibliometric approach. A vast range of literature is covered by the analysis, including foundational works on political ecology, institutional ecology, ecological footprint, sustainable rural lifestyles, and systems thinking. Through the identification of clusters within the literature, the study reveals important topics including the preservation of biodiversity, sustainable tourism, and the incorporation of indigenous knowledge. The Brundtland Report and